Erythrocyte‐exchange with the OPTIA™ cell separator in patients with sickle‐cell disease. Issue 6 (2nd September 2013) - Perseghin, Paolo; Incontri, Arianna; Capra, Manietta; Pichler, Herbert; Witt, Volker
<x xml:space="preserve">Abstract</x> Erythrocyte–exchange (EEX) has proven to be a very useful tool in sickle‐cell disease (SCD) patients either during acute painful crisis unresponsive to hydration and/or analgesia or as a prophylactic treatment in high risk patients in those who do not tolerate hydroxyurea (HU), with the aim of lowering HbS levels. EEX may be performed either by using continuous‐ or discontinuous flow devices, the former being of choice in children or in low‐weight patients. Thus, a low extracorporeal blood volume (EBV) could allow for a better and safer procedure management. In this study we compared EEX procedure performed with the recently released OPTIA device with EEX procedures performed using the COBE Spectra device (EBV 185 vs 270 mL, respectively). Twenty‐one EEX (4 as emergency treatment) were performed in 12 patients with the Spectra device and 25 (9 as emergency treatment) in 15 patients with the OPTIA device. All the procedures were well tolerated and uneventful. We did not observe significant differences between the two devices as to pre‐ and post‐EEX parameters, namely in target hematocrit and in HbS reduction. Noteworthy, due to the lowest EBV allowed by the OPTIA device, an EEX procedure performed in a 13 Kg‐ child did not require a preliminary priming of the circuit. In conclusion, the OPTIA device proved to be as effective as the Spectra device in treating SCD patients either during sickling crisis or as prophylactic therapy. The OPTIA device can be safely used in the pediatric setting since it allows a lower EBV. J. Clin. Apheresis, 28:411–415, 2013. © 2013 Wiley Periodicals, Inc.